Proteomic Changes Associated With Sperm Fertilizing Ability in Meat-Type Roosters - Vitorino Carvalho, Anaïs; Soler, Laura; Thélie, Aurore; Grasseau, Isabelle; Cordeiro, Luiz; Tomas, Daniel; Teixeira-Gomes, Ana-Paula; Labas, Valérie; Blesblois, Elisabeth (Frontiers in Cell and Developmental Biology, 2021)
Molecular basis of male fertility remains unclear, especially in chickens, where decades of genetic selection increased male fertility variability as a side effect. As transcription and translation are highly limited in sperm, proteins are key molecules defining their functionality, leading proteomic approaches as ones of the most adequate methods to investigate sperm capacity. In this context, it is interesting to combine complementary proteomic approaches to maximize the identification of proteins related to sperm fertilizing ability. In the present study, we aimed at identifying proteins related to fertility in meat type roosters, showing fertility variability. Fertile roosters (fertility rates higher than 70% after artificial insemination) differed from subfertile roosters (fertility rates lower than 40%) in their sperm mass motility. Fertile and subfertile sperm protein contents were compared using two complementary label-free quantitative proteomic methods: Intact Cell MALDI-TOF-Mass Spectrometry and GeLC-MS/MS. Combining the two strategies, fifty-seven proteins were identified as differentially abundant. Most of them were described for the first time as differentially abundant according to fertility in this species. These proteins were involved in various molecular pathways including flagellum integrity and movement, mitochondrial functions, sperm maturation and storage in female tract as well as oocyte-sperm interaction. Collectively, our data improved our understanding of chicken sperm biology by revealing new actors involved in the complexity of male fertility that depends on multiple cell functions to reach optimal rates. This explains the inability of reductionist in vitro fertility testing in predicting male fertility and suggest that the use of a combination of markers is a promising approach.